Zastosowanie modelu ryzyka Value at Risk (VaR) opartego na metodzie Monte Carlo do rynku nieruchomości - Krawczyk, Ewa (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2006)
Value at Risk – the method emerged several years ago that measures potential loss at a given confidence level. The method is undergoing continous improvment, finding new use in financial institutions. Investment briefcase management is inseparably connected with risk mamagement – process succured today with risk models. Presented attempt of enforcing specialized tool for measuring defined risk for separeted risk on property market analysis gives following remarks: 1. In the situation of considerable growth of investition on property market, which is financed mainly from bank infestations, there is need to make out risk models which describes market segment behaviour and let to limit possible loss. The loss caused by overoptimistic predictions and wrong costeffectiveness calculation. 2. Well-known and used at financial market risk models are great tools to connect both segments of market – financial and objective – and for empiric verification including investment projects. 3. VaR model may be used for the needs of defined risk of separeted investment project, which is characterized by indicator of profitability (NP), but obtained results should be treatened with limited confidence